2021
DOI: 10.1186/s12959-021-00342-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral anticoagulation therapy on postoperative atrial fibrillation outcomes: a systematic review and meta-analysis

Abstract: Background Post-operative atrial fibrillation (POAF) is the most common complication after cardiac surgery. Recent studies had shown this phenomenon is no longer considered transitory and is associated with higher risk of thromboembolic events or death. The aim of this study was to systematically review and analyze previous studies comparing oral anticoagulation therapy with no anticoagulation, regarding these long-term outcomes. Methods PubMed/MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
7
0
2
Order By: Relevance
“…5,6 A review of 8 observational studies that included 15 335 patients found a protective impact on the mortality rate at 5 years but no differences in thromboembolic events in patients with postoperative AF treated with anticoagulants. 7 In general, the duration of anticoagulation is a minimum of 60 days; in the randomized trial of rate control versus rhythm control, if patients remained in AF or had recurrent AF 48 hours after randomization, anticoagulation was recommended to be continued for 60 days, unless complications occurred. Patients should be evaluated before discontinuation to determine underlying rhythm, especially those at high risk for stroke. The need for a rhythm-control strategy should be evaluated postdischarge.…”
Section: Af and Specific Patient Groupsmentioning
confidence: 99%
“…5,6 A review of 8 observational studies that included 15 335 patients found a protective impact on the mortality rate at 5 years but no differences in thromboembolic events in patients with postoperative AF treated with anticoagulants. 7 In general, the duration of anticoagulation is a minimum of 60 days; in the randomized trial of rate control versus rhythm control, if patients remained in AF or had recurrent AF 48 hours after randomization, anticoagulation was recommended to be continued for 60 days, unless complications occurred. Patients should be evaluated before discontinuation to determine underlying rhythm, especially those at high risk for stroke. The need for a rhythm-control strategy should be evaluated postdischarge.…”
Section: Af and Specific Patient Groupsmentioning
confidence: 99%
“…This, taken with recurrence rates below 50% suggest that identification of POAF alone is not sufficient to identify patients that would benefit from lifelong OAC therapy. This is further supported by a systematic review that failed to show a decrease in the risk of thromboembolic events with the use of OAC following POAF ( 10 ) and is reflected by the contemporary European Society of Cardiology Guidelines ( 1 ). At this time there are not clear data to guide the risk stratification and selection of patients with POAF that would benefit from OAC.…”
Section: Discussionmentioning
confidence: 80%
“…En nuestro conocimiento, este metaanálisis es el primero que evalúa los resultados en pacientes con fibrilación auricular posoperatoria de novo que recibieron tratamiento con anticoagulantes orales directos comparados con aquellos que recibieron warfarina. Otras revisiones sistemáticas similares han estudiado estos desenlaces, pero incluyeron todos los tipos de anticoagulantes (parenterales y orales) 24 , otro estudio incluyó pacientes con antecedente de FA antes de cirugía cardiaca 25 y otro incluyó la comparación contra el no uso de anticoagulantes 26 . Se hallaron 5 estudios que cumplieron los criterios de inclusión y compararon desenlaces entre los dos grupos de tratamiento en términos de mortalidad, eventos isquémicos, sangrado y costos, para un total de 27.709 pacientes analizados.…”
Section: Discussionunclassified
“…Aunque en un metaanálisis, que incluyó los estudios pivotales de los anticoagulantes orales directos contra warfarina, se mostraron menores tasas de mortalidad por todas las causas a favor de los anticoagulantes orales directos, la mayoría de estos estudios no tuvieron poder estadístico para establecer diferencias en resultados secundarios y en subgrupos, y sólo se evidenciaron menores tasas de mortalidad con el uso de apixabán y bajas dosis de edoxabán 9 . Por su parte, la fibrilación auricular posoperatoria por sí sola aumenta la tasa de mortalidad en los pacientes que la desarrollan 31 y el tratamiento con anticoagulantes orales mostró disminuir todas las causas de mortalidad en estos pacientes cuando se les hizo seguimiento a 5 años aproximadamente, según datos reportados en un metaanálisis de Fragao-Marques 26 .…”
Section: Discussionunclassified